The Influence of Valence on the Peculiarities of the use of Marked and Unmarked Adverbs - Nabiyev, Alisher Isomiddinovich (European Journal of Life Safety and Stability (2660-9630), 2022)
this article deals with the influence of valence on the peculiarities of the use of marked and unmarked adverbs, author provides several examples on valence and gives notions of prominent linguists.